School guidance teams and health promotion : Analysis from the direction of community psychology and social pedagogy’s management - Noriega, Javier (2018)
The aim of the following paper is to characterize and analyze the intervention practices in prevention and health promotion carried on by school guidance teams in La Plata discrict. Is a transactional decriptive study with qualitative approach. The analytical procedure focused on the analysis of interpretive content present in a series of semi directed in-depth interviews with key actors of the Community Psychology and Social Pedagogy’s Direction of Buenos Aires province. The investigation points to establish the necessary conditions to transform public schools into Health Promotion Schools identifying the dimensions that involve specifically the school guidance teams. Interview analysis indicates an emphasis in characterize the school guidance teams as teachers. This is counter productive for establishing health promoting practices within schools because leaves health mostly as an outside dimension. An overlapping between integral sex education and health education activities is identified. On the other hand, community operations carried on by the school guidance teams are established as the articulation between the school and other institutions of the community in solving various problems without establishing the specificities of implementing those operations within schools. Finally, an emphasis in professionalization through situated practice for the school guidance team members is identified. This could be an advantage in orienting their activity to health promotion because their training depends on the work they carry on in the school regardless of their graduate training. This implies that the configuration of training documents, regulations and experiences would have a strong impact in orienting their activity to health promotion.